Functional Analyses of the EBNA1 Origin DNA Binding Protein of Epstein-Barr Virus - Ceccarelli, Derek F. J. (American Society for Microbiology, 2000)
The EBNA1 protein of Epstein-Barr virus (EBV) governs the replication and segregation of the viral episomes in latently infected cells and transactivates the expression of other EBV latency proteins through direct interactions with DNA sequences in the EBV latent origin of replication, oriP. To better understand how EBNA1 controls these processes, we have assessed the contribution of various EBNA1 sequences to its replication, segregation, and transactivation functions. Here we show that EBNA1 residues 325 to 376 are responsible for the transactivation activity of EBNA1. This region coincides with the DNA looping domain previously shown to mediate interactions at a distance between DNA-bound EBNA1 molecules. The same residues mediate DNA segregation but have no apparent role in DNA replication, indicating that the replication and transcription activation activities of EBNA1 are distinct. The acidic C-terminal tail of EBNA1 was not found to contribute to replication, transactivation, or segregation. We have also investigated the functional significance of two structural motifs within the DNA binding and dimerization domains of EBNA1, the proline loop and the WF motif. Although the amino acids in these motifs do not directly contact the DNA, both of these motifs were found to contribute to EBNA1 functions by increasing the DNA-binding ability of EBNA1. Mechanisms by which DNA binding is stimulated by these motifs are discussed.